2015
DOI: 10.1080/23723556.2015.1033587
|View full text |Cite
|
Sign up to set email alerts
|

Δ113p53/Δ133p53 converts P53 from a repressor to a promoter of DNA double-stand break repair

Abstract: In response to DNA damage, p53 (TP53, best known as p53) is quickly activated leading to cell cycle arrest or apoptosis to ensure genomic integrity; however, this represses DNA double-strand break (DSB) repair. Our recent work revealed that Δ113p53/Δ133p53 protein is accumulated at a later stage upon DNA DSB stress to switch p53 signaling from repression to promotion of DNA DSB repair.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 10 publications
0
5
0
Order By: Relevance
“…Besides, S100A4 participated in the regulation of Cisplatin-resistance of different cancer cells in a p53-dependent manner [27,28]. Since Cisplatin promoted cancer cell death and inhibited cell viability by inducing DNA double-strand break (DSB) [29,30], and p53 was the hub gene of DSB-induced cell death [31], it was reasonable to hypothesize that S100A4/p53 axis was crucial for regulating Cisplatinresistance of CC cells. Interestingly, previous study found that miR-149-3p inhibited bladder cancer cell proliferation and migration by downregulating S100A4 expression levels [15], which indicated that S100A4/p53 axis might be regulated by miR-149-3p.…”
Section: Introductionmentioning
confidence: 99%
“…Besides, S100A4 participated in the regulation of Cisplatin-resistance of different cancer cells in a p53-dependent manner [27,28]. Since Cisplatin promoted cancer cell death and inhibited cell viability by inducing DNA double-strand break (DSB) [29,30], and p53 was the hub gene of DSB-induced cell death [31], it was reasonable to hypothesize that S100A4/p53 axis was crucial for regulating Cisplatinresistance of CC cells. Interestingly, previous study found that miR-149-3p inhibited bladder cancer cell proliferation and migration by downregulating S100A4 expression levels [15], which indicated that S100A4/p53 axis might be regulated by miR-149-3p.…”
Section: Introductionmentioning
confidence: 99%
“…The human gene TP53 expresses 12 different p53 isoforms with varied sequences and properties. The p53C is the predominant constituent of the isoforms ⌬133p53␤, ⌬133p53␥, ⌬160p53␤, and ⌬160p53␥ (7), which play significant roles in the regulation of full-length p53 expression (8) and behavior in cancerous and normal cells (9,10). Their relative mRNA expression varies in different tissues and has been correlated to stress response and p53 activation (11).…”
mentioning
confidence: 99%
“…In comparison, the oncogenic role of the Δ160p53 isoform in human cancers is less explored 11 , although links have been established between the expression of Δ160p53 isoform and melanoma cells 30 . The mechanisms of the oncogenic potential of p53 isoforms have attracted increasing attention from researchers 14,59,60,61,62,63 . A theory of the dominant-negative effect has been introduced, but its exact details have remained unknown.…”
Section: Discussionmentioning
confidence: 99%